Inhaled nitric oxide: can it serve as a savior for COVID-19 and related respiratory and cardiovascular diseases? - Zhao, Yifan; Li, Cheng; Zhang, Shuai; Cheng, Jiayu; Liu, Yucheng; Han, Xiaorong; Wang, Yinghui; Wang, Yonggang (Frontiers in Microbiology, 2023)
Nitric oxide (NO), as an important gaseous medium, plays a pivotal role in the human body, such as maintaining vascular homeostasis, regulating immune-inflammatory responses, inhibiting platelet aggregation, and inhibiting leukocyte adhesion. In recent years, the rapid prevalence of coronavirus disease 2019 (COVID-19) has greatly affected the daily lives and physical and mental health of people all over the world, and the therapeutic efficacy and resuscitation strategies for critically ill patients need to be further improved and perfected. Inhaled nitric oxide (iNO) is a selective pulmonary vasodilator, and some studies have demonstrated its potential therapeutic use for COVID-19, severe respiratory distress syndrome, pulmonary infections, and pulmonary hypertension.In this article, we describe the biochemistry and basic characteristics of NO and discuss whether iNO can act as a "savior" for COVID-19 and related respiratory and cardiovascular disorders to exert a potent clinical protective effect.